The THE USE OF GUESSING GAME TO IMPROVE SPEAKING ABILITY AT THE EIGHT CLASS STUDENTS OF SMPN 1 BONTONOMPO SELATAN GOWA - Nur Ulfayanti; Nur Qalbi Qalbi; Yassir Mallapiang (FKIP Unismuh Makassar, 2022)
This study aimed to determine the improvement of students speaking ability after using the guessing game that in the process of teaching and learning speaking, teachers can bring real objects according to the theme of lessons. This research focuses to noun vocabulary,pronunciation,and fluency.The researcher applied the pre-xperimental method, consist of pre-test treatment, and post-test design, and collected the data by giving pre-test and posttest. The sample of the research was class VII A SMPN 1 Bontonompo Selatan which consisted of 16 students. The sample was taken by using guessing game method.The result of the research showed score in the pre-test was 41, and in the post-test was 75,44. In this research also show that The value t-test was higher than the value of the t-table (27,04>1.713 ). It mean that the alternative hypothesis (H1) was accepted and the null hypothesis (H0) was rejected. It was concluded the implementation of guessing game in VII grade of SMPN 1 Bontonompo Selatan was effective to improve students’ speaking ability.